Reforming the international financial system - Ang, Choon Wee (2008)
This report seeks to investigate the causes of the recent financial crisis. It first explain why international financial markets should be reformed in light of the depth and severity of the crisis, folloed by proposals on how they should be reformed to mitigate if not prevent future economic crisis.